2011
DOI: 10.3382/ps.2011-01473
|View full text |Cite
|
Sign up to set email alerts
|

Time course changes in selected biochemical indices of broilers in response to pretransport handling

Abstract: Two experiments were conducted to assess the stress response of broilers to catching and pretransport handling followed by different periods of crating. The short-term changes in selected biochemical indices were monitored at 1-min intervals within 10 min of crating after the catching and handling of broilers (experiment 1). These indices were further monitored at 15-min intervals for 2 h of crating after the catching and handling of broilers (experiment 2). Increased (P < 0.001) corticosterone concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 36 publications
2
30
1
1
Order By: Relevance
“…On the contrary, Kannan et al (1997) did not observe any effect of different crating durations on plasma corticosterone concentrations, yet they suggested that holding broilers for 4 h in a dark, quiet place after transportation could reduce stress responses. Glucose concentrations were reported to increase for 2 min following the crating, but decreased thereafter to similar values of the control birds (Voslarova et al, 2011).…”
Section: Catching and Loadingmentioning
confidence: 91%
See 3 more Smart Citations
“…On the contrary, Kannan et al (1997) did not observe any effect of different crating durations on plasma corticosterone concentrations, yet they suggested that holding broilers for 4 h in a dark, quiet place after transportation could reduce stress responses. Glucose concentrations were reported to increase for 2 min following the crating, but decreased thereafter to similar values of the control birds (Voslarova et al, 2011).…”
Section: Catching and Loadingmentioning
confidence: 91%
“…However, Nijdam et al (2005b) reported higher corticosterone levels after transportation, shackling, and stunning (115%) compared to immediately after catching (75%). Voslarova et al (2011) showed a continued increase in corticosterone levels for 7 min after placing birds into the crates, where it started to decrease, but not to the values of the non-crated birds even after 2 h. Chloupek et al (2008) reported a 3-fold increase in corticosterone concentration after a 4-h crating period. On the contrary, Kannan et al (1997) did not observe any effect of different crating durations on plasma corticosterone concentrations, yet they suggested that holding broilers for 4 h in a dark, quiet place after transportation could reduce stress responses.…”
Section: Catching and Loadingmentioning
confidence: 93%
See 2 more Smart Citations
“…It is well established that serum corticosterone levels are directly related to stress intensity (Voslarova et al, 2011), and therefore, should be determined when evaluating the effects of thermal stress. Moreover, corticosterone is also a critical endogenous factor affecting overall embryo metabolism and behavior (Tong et al, 2013).…”
Section: Effect Of Embryo Thermal Stimulation On the Serum Levels Of mentioning
confidence: 99%